2010
DOI: 10.1074/jbc.m109.087213
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of the Human Nicotinic Acid Receptor GPR109A Is Regulated by Gi, GRK2, and Arrestin3

Abstract: Nicotinic acid (niacin) has been widely used as a favorable lipid-lowering drug for several decades, and the orphan G protein-coupled receptor GPR109A has been identified to be a receptor for niacin. Mechanistic investigations have shown that as a G i -coupled receptor, GPR109A inhibits adenylate cyclase activity upon niacin activation, thereby inhibiting free fatty acid liberation. However, the underlying molecular mechanisms that regulate signaling and internalization of GPR109A remain largely unknown. To fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 59 publications
3
63
1
Order By: Relevance
“…This is followed by recruitment of GRK2 to catalyze phosphorylation of the activated receptors. GRK2-mediated phosphorylation promotes the binding of arrestin3, targeting receptors to clathrin-coated pits and causing their internalization (Li et al, 2010). Using arrestin2/3-specific siRNAs and an internalization-deficient HCA 2 mutant, we found that arrestin2 and arrestin3 are not involved in HCA 2 -mediated ERK1/2 activation (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is followed by recruitment of GRK2 to catalyze phosphorylation of the activated receptors. GRK2-mediated phosphorylation promotes the binding of arrestin3, targeting receptors to clathrin-coated pits and causing their internalization (Li et al, 2010). Using arrestin2/3-specific siRNAs and an internalization-deficient HCA 2 mutant, we found that arrestin2 and arrestin3 are not involved in HCA 2 -mediated ERK1/2 activation (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…For fluorescence detection experiments, the cDNA of the HCA 2 receptor was C-terminally fused to the cDNA of enhanced green fluorescent protein (EGFP). To perform enzyme-linked immunosorbent assays (ELISA) for quantification of receptor expression and internalization, the cDNA of the HCA 2 receptor was inserted between the HindIII and EcoRI sites of the pCMV-FLAG vector as described previously (Li et al, 2010). Mutations and truncations were introduced by overlap extension polymerase chain reaction.…”
Section: Methodsmentioning
confidence: 99%
“…The GPR109A receptor for niacin was identified on human platelets by flow cytometry (Supplemental Figure 8A) and immunofluorescent staining, predominately of the cell membrane (Supplemental Figure 8, B and C). Niacin-induced degradation of its receptor, as observed in other cell types (43), was apparent on Western blotting of platelet cell membranes (Supplemental Figure 8D). Niacin dose-dependently decreased platelet cyclic AMP, as expected, upon activation of this Gi-linked receptor (ref.…”
Section: Figurementioning
confidence: 99%
“…The full agonist nicotinic acid induced internalization, whereas a partial agonist (which, unlike nicotinic acid, did not induce ERK phosphorylation) had no effect . Internalization of heterologously expressed HCA 2 activated by nicotinic acid was shown to occur in a manner dependent on G-protein-coupled receptor kinase 2 (GRK2) and arrestin 3, whereas the recycling of the internalized receptor was independent of endosomal acidification (Li et al, 2010).…”
Section: Receptor Desensitizationmentioning
confidence: 99%
“…However, whether these desensitization phenomena are due to effects on the receptor itself or are at the level of downstream signaling processes is not clear. For heterologously expressed HCA 1 and HCA 2 receptors, internalization of the receptor in response to ligand application has been described previously Liu et al, 2009;Li et al, 2010). In the case of heterologously expressed HCA 2 receptor, internalization is dependent on the type of ligand.…”
Section: Receptor Desensitizationmentioning
confidence: 99%